2011
DOI: 10.1055/s-0030-1256305
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic 5-Fr pancreatic duct stents are superior to 3-Fr stents: a randomized controlled trial

Abstract: Background Temporary prophylactic pancreatic duct stenting effectively reduces post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) in high-risk patients, but the optimal stent remains unclear. We compared rate of spontaneous passage, and technical difficulty of placement for 3-Fr and 5-Fr stents. Methods A randomized controlled trial at a single academic medical center. Patients deemed high risk for PEP randomly received 5-Fr or 3-Fr pancreatic duct stents. Primary outcome was spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 18 publications
1
51
2
Order By: Relevance
“…A higher rate of PS placement failure and PEP, but without statistical difference (14% in 3F group and 9% in 5F group), was observed in patients with 3F stents. Recently, Zolotarevsky et al 18 reported that placement of a 5F compared with a 3F PS for PEP prophylaxis is easier and faster and requires fewer wires. However, there was no statistically significant difference in spontaneous passage rates (5F group, 68.4%; 3F group, 75.0 %; P ϭ .617) and PEP rates (P ϭ .519).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A higher rate of PS placement failure and PEP, but without statistical difference (14% in 3F group and 9% in 5F group), was observed in patients with 3F stents. Recently, Zolotarevsky et al 18 reported that placement of a 5F compared with a 3F PS for PEP prophylaxis is easier and faster and requires fewer wires. However, there was no statistically significant difference in spontaneous passage rates (5F group, 68.4%; 3F group, 75.0 %; P ϭ .617) and PEP rates (P ϭ .519).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Recent studies reported that prophylactic placement of a pancreatic stent (PS) reduces the frequency and severity of PEP in various risk groups, including those with known or suspected sphincter of Oddi dysfunction (SOD), papillectomy, precut sphincterotomy, pancreatic sphincterotomy, history of PEP, or a difficult cannulation. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The overall success rate for selective cannulation during ERCP ranges from 90% to 95%, even when performed by experts. 7 During biliary cannulation, the rate of PEP increases when cannulation is difficult and prolonged.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two meta-analyses about prophylactic pancreatic stenting for the prevention of post-ERCP pancreatitis showed a significant decrease of either the odds ratio to 0.22 or the relative risk to 0.32 [19,20]. Another randomized study showed the superiority of a 5-Fr stent over a 3-Fr stent in this indication [21]. Thus, a pancreatic prosthesis appears to be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis, PEP rates were similar in patients who received 4 French or 5 French stents but spontaneous migration rate was significantly higher in the 4 French group [57]. More recently however, a randomized trial comparing 5 French to 3 French stents was terminated early for futility, since no difference was noted in the primary outcome of stent migration [58]. Three French stents do not appear to impart a large advantage in migration rate, and are significantly more difficult to place, limiting their suitability in the setting of prophylactic pancreatic stenting.…”
Section: Mildmentioning
confidence: 99%